2020
DOI: 10.2147/ijn.s241922
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative Toxicological Effects of Biologically and Chemically Synthesized Copper Oxide Nanoparticles on Mice</p>

Abstract: Introduction:Copper oxide nanoparticles (CuO-NPs) are widely used as feed additives for livestock and poultry and implicated in many biomedical applications; however, overload of copper NPs induces various toxicological changes and dysfunction of animal's organs. Thus, this study was designed to evaluate the comparative toxicological effects of biologically and chemically synthesized CuO-NPs on mice. Methods: Transmission electron microscopy (TEM), X-ray diffraction (XRD) and Fouriertransform infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 53 publications
4
22
0
Order By: Relevance
“…On the other hand, G4 clarified diffuse immuno-localization of caspase-3 that was widely expressed in almost of the hepatic parenchyma confirming widespread of apoptosis. These findings were confirmed by El Bialy et al (2020) who clarified that the hepatocytes of mice administered biologically synthesized CuO NPs showed marked caspase-3 immunostaining Regarding the histological examination, the kidney of G2 and G3 characterized with moderate necrosis and atrophy of renal corpuscles, damage of Bowman's capsules, swelling and congestions of the glomerulus, mild to moderate necrosis of the renal tubules with moderate damage in its lining epithelium accompanied with loss of its brush border. And also, acidophilic granules of variable shape and size were accumulated within the renal tubules lining epithelium and extended to the lumen of renal tubules.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, G4 clarified diffuse immuno-localization of caspase-3 that was widely expressed in almost of the hepatic parenchyma confirming widespread of apoptosis. These findings were confirmed by El Bialy et al (2020) who clarified that the hepatocytes of mice administered biologically synthesized CuO NPs showed marked caspase-3 immunostaining Regarding the histological examination, the kidney of G2 and G3 characterized with moderate necrosis and atrophy of renal corpuscles, damage of Bowman's capsules, swelling and congestions of the glomerulus, mild to moderate necrosis of the renal tubules with moderate damage in its lining epithelium accompanied with loss of its brush border. And also, acidophilic granules of variable shape and size were accumulated within the renal tubules lining epithelium and extended to the lumen of renal tubules.…”
Section: Discussionmentioning
confidence: 65%
“…A high dose of biologically and chemically synthesized CuO nanoparticles induced adverse effects on hepatic, renal and splenic tissues. At the same dose level, the biologically synthesized CuO nanoparticles evoked more potent toxic effects than the chemically synthesized ones [177]. Particularly, it has been confirmed that MONPs may induce serious genotoxic effects on various biological targets.…”
Section: Fluorescence Detection Of Transition Metal Oxide Nanoparticlesmentioning
confidence: 91%
“…Similarly, the rats developed significant liver and kidney damage, mainly manifested as elevated alanine aminotransferase and aspartate aminotransferase, creatinine, and blood urea nitrogen when given continuous intragastric administration of Cu–NPs for 5 days at a dose of 200 mg/kg body weight . In total, overload of CuO–NPs and Cu–NPs can induce gastrointestinal, hepatic, renal, neuronal, and splenic toxicities through the generation of ROS and depletion of antioxidants in mammals. , In human cells, NPs are closely linked to cardiovascular diseases . Fan et al reported that CuO–NPs exposure disturbs the mitochondrial dynamics in an oxidative stress-dependent manner and induced mitophagy in vascular endothelial cells.…”
Section: Application and Toxicity Of Copper-based Nanoparticlesmentioning
confidence: 99%